2005
DOI: 10.1002/gene.20155
|View full text |Cite
|
Sign up to set email alerts
|

Differing strategies of patterning of follicular cells in higher and lower brachycerans (Diptera: Brachycera)

Abstract: In all higher dipterans (Brachycera), including the fruitfly, Drosophila melanogaster, each egg chamber (ovarian follicle) consists of a group (clone) of germ cells (one oocyte and 15 accompanying nurse cells) that is surrounded by a layer of somatic mesodermal follicular cells (FCs). As oogenesis progresses the initially uniform FCs diversify into several morphologically and functionally distinct subpopulations. In D. melanogaster some of these subpopulations, e.g., border, centripetal, and dorsolateral cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 30 publications
1
36
1
Order By: Relevance
“…The ovarian follicles of the species investigated in this study (see Table 1) were processed for the light, fluorescent and electron microscopy analysis as previously described (see Tworzydlo et al 2005 for details). In each species, FC diversification has been examined in two to four ovarian follicles at the same stage of development.…”
Section: Methodsmentioning
confidence: 99%
“…The ovarian follicles of the species investigated in this study (see Table 1) were processed for the light, fluorescent and electron microscopy analysis as previously described (see Tworzydlo et al 2005 for details). In each species, FC diversification has been examined in two to four ovarian follicles at the same stage of development.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, in the egg chambers of lower brachycerans, the border cells migration is facilitated by the progressive degradation of the nurse cell complex. No other translocations of FCs have been described in lower brachycerans (Kubrakiewicz et al, 2003, Tworzydlo et al, 2005. Their FCs neither stretch nor migrate centripetally, but rather maintain their position within the epithelium throughout oogenesis.…”
Section: Discussionmentioning
confidence: 97%
“…Their FCs neither stretch nor migrate centripetally, but rather maintain their position within the epithelium throughout oogenesis. Tworzydlo et al (2005) reported that the FCs in lower brachycerans may change their relative position within the epithelium. This change, however, does not result from the FCs migratory activity, but depends on the specific behaviour of the oocyte.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations